Sports profile of elite athletes in rhythmic gymnastics - Ivanova, I. V. (Science of Gymnastics Journal, 2021)
Elite athletes are competitors who combine in themselves exceptional talent, many years of hard work and distinctive psychological qualities. Highly qualified rhythmic gymnasts do not differ from this definition, as their sports profile includes all these characteristics. The aim of this study is to develop a methodology to create the sports profile of elite competitors in rhythmic gymnastics on the basis of current competitors from the USA, Singapore and Taiwan and to compare the obtained results. This could help us assess the current habits of these gymnasts, the positive or negative impact of those habits on their performance, and the necessary changes that need to be made to optimize the training process. The results of the current study and the statistical data processing from the conducted experiment showed that the three studied teams of elite athletes (total of 63 gymnasts) demonstrated strong commitment and engagement in the training process. Generally, the Singaporean and Taiwanese athletes had difficulties in communication with their coach and lagged behind in the development of technical qualities and mental skills for effective adaptation compared to their colleagues from the United States. At the same time, however, they showed a higher degree of self-awareness for improvement. On the other hand, the athletes from the US demonstrated shortcomings in Consistency in training. The numerical values also showed that some of the US athletes demonstrated limitations in the development of physical qualities which could affect their professional sports development in the future.